Unrecorded Waqf Land: A Socio-Legal Study of the Phenomenon of Security without Administration - Dalimunthe, Muhammad Alwi; Habib, Abdul (Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2025)
Waqf land plays an important role in the social and economic development of the community, but its administrative registration is still an obstacle. This study examines the phenomenon of unregistered waqf land but free from disputes in Kepenghuluan Pondok Kresek, Kepenghuluan Tanjung Sari, and Kepenghuluan Sri Kayangan, Tanjung Medan District, Rokan Hilir, Riau. This study aims to identify factors that cause unregistered waqf land, understand social, cultural, and legal influences, and provide recommendations to increase awareness of the importance of recording waqf land. The research method used is a qualitative approach with a socio-legal method. Data were collected through in-depth interviews, observations, and related document studies. The results and conclusions of this study indicate that the main factors for unregistered waqf land are the lack of understanding of waqf law in the community, the lack of socialization from PPAIW, and the strong customary customs that consider waqf valid without registration. Oddly enough, no waqf land disputes were found in the area, due to the role of traditional leaders and the high level of community trust in the traditional system. This study recommends increasing the socialization of waqf law and facilitating the registration of waqf land.